Isotopic composition of oxygen and hydrogen of ice wedges in Central Yamal - Ju. N. Chizhova; E. M. Babkin; A. V. Khomutov (Лëд и снег)
New data on the distribution of the isotopes δ18О and δD of ice wedges in Central Yamal are presented. In the summer of 2019, the massive wedge ice was studied in the thermal circus of the third marine terrace. On the surface of the terrace, polygonal-vein relief is common with a polygon size of about 10–20 m. The largest ice wedge № 1 in the upper part was 1.5 m wide, and its visible depth in the outcrop amounted to 2.3 m. Perpendicular to this wedge, another one № 2 was opened with a width of 60 cm, and 20 m from them the wedge № 3 was opened along the strike. At the level of the head of the wedge № 1, radiocarbon AMS dating was performed based on a sample of host deposits, which showed that the ice in the upper part was about 13 thousand years old (the ice age was of 13.6 cal. BP). According to the isotopic characteristics (average values of δ18О = −24.8, and δD = −187.6 ‰), the ice corresponds to the Yamal ice-wedge ice, which was formed during the MIS‑2 isotopic stage (the end of the Late Pleistocene). The isotopic composition of oxygen indicates temperatures of the cold period of the vein formation from −22.8 to −26.8 °C (on average 7 °C colder than the present-day) and the January temperatures from −34.2 to −40.2 °C (on average 10 °C colder than the present-day). For some ice samples (11 out of 43), high values of deuterium excesses (dexc = 12÷17 ‰) were observed, which is unusual for this type of ice. A few examples of high dexc values of ice wedges are mentioned in the literature for sections of Seyakha yedoma, Cape Sabler and Bolshoi Lyakhovsky Island, and note that for the ice dated to the Late Pleistocene. The deuterium excess values may reflect the unstable climatic conditions of the Late Pleistocene associated with changes in the vapor source and the trajectories of the air masses over the continent.